Rekonstruksi Ekoteologi Berbasis Pemikiran Al-Ghazali dan Relevansinya Bagi Krisis Ekologi Modern : The Reconstruction of Ecotheology Based on Al-Ghazali's Thought and Its Relevance to the Modern Ecological Crisis - Uup Gufron; Kartono (Jurnal Bimas Islam, 2026)
Indonesia’s current ecological condition is highly alarming, primarily due to human behavior and the way of thought in interacting with nature. A spiritual void characterizes the ways in which nature is enjoyed, managed, and exploited. The floods and landslides that occurred in Sumatra and Aceh in late 2025 serve as a serious indication of the disharmony between human and the natural environment. The environmental crisis thus reflects a deeper spiritual crisis. This study aims to reconstruct Al-Ghazali’s eco-theological thought and to position his spiritual–ethical framework as a conceptual foundation for responding to the modern ecological crisis, which tends to exclude the spiritual dimension of nature. Methodologically, this research employs a descriptive-analytical method with a philosophical approach to Al-Ghazali’s works related to nature, particularly Al-Hikmah fī Makhluqāt Allah, Ihyā’ ‘Ulūm al-Dīn, and Mishkāt al-Anwār. The findings reveal that: (1) the relationship between God, nature, and humans constitutes an inner spiritual interconnectedness between God, His manifestations (tajallī), and His vicegerent (khalīfah); (2) as God’s vicegerent, humans bear the trust (amānah) to preserve the sustainability of nature, including mountains and vegetation; (3) Al-Ghazali’s eco-theology emphasizes ecological simplicity (zuhd) and environmental preservation (hifẓ al-arḍ) as ethical principles in managing nature; and (4) the 2025 Sumatra–Aceh disasters may be interpreted as expressions of a spiritual crisis in humanity’s treatment of the environment. This study concludes that the human–nature relationship is not based on domination, physicality, or power, but rather on stewardship (trust), spirituality (inner awareness), and the harmony of the earth’s ecological system.